PHILOSOPHIEGESCHICHTE ALS PROBLEMFELD DER WISSENSCHAFTSLEHRE FICHTE - Stahl, Jürgen (Daimon Revista Internacional de Filosofia, 1994)
The article brings out the deeping of the immanent historical tendency emerging in Fichte's transcendental philosophy in the specific viewpoint of methodical approaches of historical-philosophical analysis. The debate with philosophical teaching is an integral moment of the structure of hys system. In this way Fichte came to a series of insights into the historicity and logic in the development of philosophy with thereby prove themselves to be a step of formation of the unity of the logical and the historical through the clasical German Idealism.